Factors influencing the level of traditional food knowledge amongst young generation / Siti Nor Fadillah Ahmad Shariff - Ahmad Shariff, Siti Nor Fadillah (2011)
This study takes a quantitative case study approach exploring the factor influence the level of traditional food knowledge. Traditional food knowledge (TFK) refers to a cultural tradition of sharing food, recipes and cooking skills and techniques and passing down that collective wisdom through generations. Through from this knowledge it is finding that there has a several factor influencing the level of traditional food knowledge such as formal learning, informal learning and social life style. The paper aims to investigate the relationship between factors influencing the level of the traditional food knowledge. The aim for this study was to determine how a young generation which is teenagers view the world of cooking and food especially on traditional food knowledge. From the reports, it shows that, young generations display a dissimilar food culture when they involve in learning which is formal and informal learning and also in social life style. The study was carried out with a total of respondent of 212 students and more specific is young generations in five secondary schools in east coast, Malaysia which is located in Temerloh, Pahang. From the result are shows that, there was no significant relationship between young generations’ factor influence and the level of traditional food knowledge. For the conclusion, the final have been conclude saying that, there have a several factor contribute to the hypotheses showing why there are no relationship at all.